Resposta de mudas de goiabeira a aplicação de fósforo - Batista, Marcos Antônio Vieira; Prado, Renato de Mello [UNESP]; Leite, Grazianny Andrade (My University, 2011)
Phosphorus is a nutrient that most limits plant growth because of its importance in nutrition and low concentration in tropical soils. The present study aimed to evaluate the response of guava to application of phosphorus. For this, the experiment was conducted in a greenhouse at UNESP, Jaboticabal Campus, with guava plants (cv. Paluma) from herbaceous plants cultivated in plastic bags (2.8 dm -3), filled with Alfissol (P = 2 mg dm -3), between November 2007 and April 2008. The treatments consisted of five doses of phosphorus (0, 100, 200, 300 and 400 mg dm -3) in the form of triple superphosphate (44% P 2O 5), arranged in a randomized block design with four replications. After 100 days of transplantation evaluated the phosphorus content in soil, dry weight of shoot and root phosphorus and zinc in the shoot. The highest production of dry weight guava was a dose of 257 g dm-3 of phosphorus and was associated with P content in soil and leaf 110 mg dm -3 and 2,3 g kg -1.
Response of guava to phosphorus application
Keywords: Phosphate fertilizer; Psidium guajava; Seedlings